E-kiosk dan Pelatihan Konten Digital Instagram untuk Peningkatan Layanan Kesehatan Klinik - Ratri Wulandari; Idhar Resmadi; Djoko Murdowo; Asep Mulyana; Rendy Pandita; Aida Andrianawati; Togar Mulya Radja (Dinamisia, 2022)
Abstract